A survey on the prevalence of common intestinal nematodes among grade 3 pupils of Barangay Mauaque Elementary School in Mabalacat, Pampanga - Navarrete, Kirby Lemuel A. (Animo Repository, 1998)
A total of two hundred twelve (212) film bottles containing fecal samples out of three hundred fifty (350) film bottles distributed were retrieved, with a 60.57 % retrieval rate, from Grade 3 pupils of Brgy. Mauaque Elementary School in Mabalacat, Pampanga. Using the Kato-Thick Smear Technique, fecal samples collected were examined under light microscopy for the prevalence of nematode infections, specifically Ascaris lumbricoides, Trichuris trichiura and hookworms (Ancylostoma duodenale / Necator americanus). The identification of the parasites was based on egg morphology. The respondents were grouped according to sex. Of the total respondents, 113 were males and 99 were females. Among the respondents, 74.53% (158) were found positive for nematode infections. The prevalence of A. lumbricoides was 41.51% (88), 48 (42.48%) and 40 (40.40%) of those were male and female respondents, respectively. T trichiura infection was recorded at 8.49% (18), 11 (9.73%) and 7 (7.07%) of those were male and female respondents, respectively. Double infections of A. lumbricoides and T. trichiura was noted in 52 respondents (24.53%), consisting of 27 males (23.89%) and 25 females (25.25%). Hookworm infections were not found among all respondents.